INTEGRASI PEMIKIRAN ISLAM DAN PERADABAN MELAYU - Maryamah, Maryamah; Nabilla Zakiyah, Andi; Dwi Oktalena, Dela; Putri, Suciani; Mayang Sari, Tri Adha (Jurnal Multidisipliner Bharasumba, 2024)
The integration of Islamic thought and Malay civilization resulted in acculturation and assimilation between the two, giving birth to a new style of Malay Islamic civilization which had its own characteristics that were different from Islamic civilization elsewhere. The dynamics of Islamic thought in the Malay region from time to time have shaped the Islamic character of Malay civilization. Islam has become a unifying factor for various Malay tribes and 'supra-identity' across geographical boundaries, ethnic sentiment, tribal identity, local Malay customs and traditions. Malay civilization in the past became one of the foundation stones of Southeast Asian civilization. It cannot be denied that the civilizations currently developing in Indonesia, Malaysia and Brunei, Singapore, Southern Thailand, Southern Philippines, Cambodia, Sri Lanka, as far as Madagascar and South Africa, are civilizations that have grown on the basis of cultural elements, some of which or almost entirely derived from living traditions originating from Malay culture.